The great carve-up: Libya's internationalised conflicts after Tripoli - Wolfram Lacher (Stiftung Wissenschaft und Politik (SWP), 2020)
The yearlong offensive on Tripoli by Khalifa Haftar's forces has suffered fatal setbacks, and Libya's conflicts are changing shape. Russia's and Turkey's attempts at carving out spheres of influence are bound to collide with the interests of other foreign powers and with the fluidity of Libya's political landscape. Haftar could face increasing challenges to his authority over eastern and southern Libya. Rivalries within the anti-Haftar alliance will also return to the fore. Foreign intervention and the deep rifts that the war has inflicted on Libyan society will be the key obstacles to a political settlement. Western states should focus on preserving Libya's unity and countering Russian influence as a matter of priority.
Keywords: 320